Publishing articles in scientific journals: a concern for research misconduct or dishonesty (fabrication, falsification and plagiarism) (Mediscope, 2017)
An area of concern in scientific research including medical research is misconduct or dishonesty like fabrication, falsification, or plagiarism in proposing, performing, or reviewing research, or in reporting research results. This article focuses on the concepts of research misconduct with the objectives to discuss briefly on the extent of problem, various forms, possible reasons; methods of detection, and prevention. It is expected that this article will encourage the leaders of academic research groups to inform their students, future researchers and research associates about the ethical responsibilities of scientific research and publications, and to insure that, when they are given the responsibility for research and consequently submitting a paper, they are fully aware of the potential consequences to themselves and to their coauthors for violations of research ethical guidelines.Mediscope Vol. 4, No. 2: Jul 2017, Page 1-4